Chemical Diversity and Pharmacological Properties of Genus Acacia - LAGNIKA, LATIFOU (My University, 2020)
The genus Acacia, an herb distributed worldwide comprises approximately 1200 species of the Fabaceae family belonging to the tribe Acacieae. Acacia species are relevance to food and ethnopharmacology and have potential therapeutic uses. This review focuses on natural compounds isolated from plants of genus Acacia and their biological activities, based on phytochemical and biological previous studies. This review list 152 chemical constituents from Acacia's species as well as their biological activities. The main compounds isolated from Acacia species are flavonoids, terpenoids and phenolic acids, accumulated mainly in leaves, pods and stem barks. The compounds isolated from Acacia species have been demonstrated to possess multiple pharmacological activities such as; antibacterial and antifungal, antioxidant, anticancer, antiparasitic, cytotoxicity and immunomodulatory properties.
Keywords: Acacia species; chemical constituents; flavonoids; terpenoids; phenolic acid; Biological activities